Assessing Hotel Cost Control Through Value Engineering: A Case Study on the Budget Hotels in a Middle-sized City in China. Issue 5 (3rd May 2016) - Yan, Qi York; Shen, Huawen James; Kong, Haiyan
Abstract : This study employed a value engineering approach to identify and evaluate the factors integral to the efficiency of operation and management of the budget hotel sector in China. A combination of qualitative panel judgments and quantitative statistics was applied in the analysis of a Chinese budget brand which is publicly listed in the USA. Findings reveal that out of the six categories of costs identified, the two items of standard room cost and energy & maintenance achieved the ideal value, while lease rental and human resources are overvalued, with franchise fee and refurbishment cost being undervalued. The implication for hotel investors as well as operators is that for the budget sector to fully realize its potential, a delicate balance needs to be obtained so that resources can be more evenly distributed and customer experiences enriched.